Behavioral Aspect: The Impact of Organization Culture and Ethicality on Internal Auditor’s Decision Making - Hussen Abdelahi, Abdi; Arumugam, Dhamayanthi; A/P Suppiah, Kahyathri (International Journal of Psychosocial Rehabilitation, 2020)
Organizational Culture also known as Corporate Culture is referred to a system of shared beliefs, values, and assumptions that guide people between what is appropriate and inappropriate behavior. Ethical culture of the organization develops to be a powerful tool for leaders to communicate the organizational values to all members of the organization. Leaders who develop and implement ethical culture will be followed by all members of the organization and make individual milestone to perform an action. The reassessed studies given in literature demonstrates the significance of organizational culture and ethicalities and how they impact the auditor’s decision-making practices as it brings about the ethical culture, leadership styles, rule of conduct and organizational artifacts and at last the way each of the components influence internal auditor’s decision making. The findings of the present study have illustrated that there is a positive relationship between the cultural and ethical factors of (Ethical culture, Leadership style, Rule of conduct, and Artifacts) with the dependent variable Internal auditor’s decision making. The present quantitative study has a significance in the area of the organizational culture and ethical development of the corporate environment and among the different perspectives that this study could be significant to includes auditor’s and managements perspective as well as academic perspectives.